Estimación de curvas de absorción de nutrientes para el cultivo de maíz híbrido (Zea mays), en tres zonas productoras de la provincia de Los Ríos - Moran Castro, Elmo Alexander (2020)
Fertilization problems in Ecuador are increasing over time, it is common to observe effects such as: loss of productive capacity, erosion and salinity in production areas. This is caused by improper use of fertilizers, or poorly designed fertilization programs specific to the corn crop. The absorption curves are a viable alternative for the correct use of fertilization programs, since they are coupled to the different agroecological conditions where it is grown. The study carried out determined that in each area a different level curve was presented for each element evaluated. This leads farmers to apply these curves by means of their agronomist consultant, to minimize nutrient losses and to increase the efficiency of these. It is known that the absorption curve is an approximate value to the real value that the corn plant uses to achieve adequate development and production. The area with the highest productive level due to the application of this equation is Babahoyo, followed by Ventana and Puebloviejo. At a general level, the results show the formation of linear curves, that is, of expression y = ax + b, for elements such as nitrogen, phosphorus and potassium. However, in elements such as magnesium and even sulfur, polynomial expression curves y = ax2 + b were determined. The use of the absorption curve guarantees an efficient use of fertilizers, avoiding losses and improving the quality of the corn production system in the evaluated areas.